2007
DOI: 10.1063/1.2815760
|View full text |Cite
|
Sign up to set email alerts
|

Targeted cell detection based on microchannel gating

Abstract: Currently, microbiological techniques such as culture enrichment and various plating techniques are used for detection of pathogens. These expensive and time consuming methods can take several days. Described below is the design, fabrication, and testing of a rapid and inexpensive sensor, involving the use of microelectrodes in a microchannel, which can be used to detect single bacterial cells electrically (label-free format) in real time. As a proof of principle, we have successfully demonstrated real-time de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Various miniaturization techniques have been introduced for detection of proteins [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], nucleic acids [10,16,21], and cells [22][23][24][25][26][27]. These techniques are unsuitable for metabolites because tagging the metabolite with beads or a fluorophore would alter the structure significantly and affect the binding of the target metabolite to the probe antibody.…”
Section: Metabolite Detectionmentioning
confidence: 99%
“…Various miniaturization techniques have been introduced for detection of proteins [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], nucleic acids [10,16,21], and cells [22][23][24][25][26][27]. These techniques are unsuitable for metabolites because tagging the metabolite with beads or a fluorophore would alter the structure significantly and affect the binding of the target metabolite to the probe antibody.…”
Section: Metabolite Detectionmentioning
confidence: 99%
“…In a previous study, we have demonstrated the ability of this technique to detect target cells without the need for any labeling [22]. We have demonstrated the detection selectivity of this technique for glycoprotein–glycoprotein interactions, antibody-antigen interactions, and also antigen-glycoprotein interactions by choosing specific examples.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study we had demonstrated the ability of this technique to detect target cells without the need for any labeling 31. The purpose of this study was to investigate use of the described technique for specific protein biomarker detection.…”
Section: Introductionmentioning
confidence: 99%